24 Validation of swine enteroids as a model to study Lawsonia intracellularis pathogenesis. (5th December 2019) - Medida, Ramya Lekha; Resende, Talita P; Gebhart, Connie; Saqui-Salces, Milena
Abstract: Lawsonia intracellularis is an obligate intracellular bacterium that causes proliferative ileitis, an enteric disease that costs more than $100 million annually to the US swine industry. Information about L. intracellualris pathogenesis is scarce due to lack of suitable in vitro models to study the infection-induced proliferative changes. L. intracellularis infection of the swine ileum has been shown to decrease the number of mucin-producing goblet cells and increase cell proliferation along with amplification of transient amplifying cells demonstrated by the expression of SOX9. The objective of this study was to validate the use of swine enteroids (three dimensional structures derived from adult intestinal stem cells) as a model to study the intestinal epithelial changes caused by L. intracellularis infection. Swine enteroids plated on transwell plate inserts to cover the surface area were infected with 10 8 L. intracellularis organisms in culture media per well and incubated at 37⁰C with atmospheric conditions of 8.0% oxygen, 8.8% carbon dioxide, and 83.2% nitrogen. Infected enteroids were collected after 7 days and gene expression levels of mucin 2 (MUC2), enterocyte marker fatty acid binding protein (FABP), endocrine marker chromogranin A (CGA), intestinal epithelium marker villin 1 (VIL1), paneth cell marker lysozyme (LYZ), proliferating cell nuclear antigen (PCNA) and SOX9 were measured. The expression of FABP and LYZ in L. intracellularis infected swine enteroids decreased by 50% and 20% respectively and the expression of SOX9 increased by 50%, with no significant changes for the levels of VIL1 and CGA. The changes observed in the infected swine enteroids reflect the profile of gene expression observed in L. intracellularis infected ileal tissue. Therefore, swine enteroids are a suitable in vitro system to study the dynamics of cell differentiation and proliferation of the intestinal epithelium induced by L. intracellularis infection.